Black seeds (Nigella sativa) medical application and pharmaceutical perspectives - Rrahman Ferizi; Mohamed F Ramadan; Qenan Maxhuni (Wolters Kluwer Medknow Publications, 2023)
Among the various medicinal plants, the black seed is emerging as a miracle herb with a rich historical background, as much research has revealed its wide spectrum of pharmacological potential. In this collection of literature, we have encountered and presented the preclinical treatment, as alternative medicine of Nigella sativa in the prevention and treatment of various diseases, as well as those that continue to be discovered by contemporary actual scientific data. Research to date has confirmed the pharmacological potential of the seed of Nigella sativa, its oil and extracts of some of its bioactive constituents, which possess remarkable pharmacological activity, in vitro and in vivo against a large spectrum of diseases, and it has been found that the use of black seed is relatively safe. Black Seed has been extensively studied for its biological activity and therapeutic potential and has been found to possess a broad spectrum of activities. Clinical trial investigations into the therapeutic effects of Nigella sativa affect the hypoglycemic, hypolipidemic, and bronchodilator effects and have passed clinical trials and received the green light to allow the next stage of clinical trials toward therapeutic drug design. However, there is still room and multidimensional research needed for prospective clinical trials in certain groups of animals before they can be applied to humans as pharmaceutical therapies.